O discurso de prosperidade financeira da religião na tevê - Carvalho, Wesley Knochenhauer (2009)
This Master’s degree dissertation was conceived as a theoretical and analytical study concerning to religious discourse out of place from its original environment, that means, from the church to TV. From the many available elements, our research works with the successful discourses involving money contributions, a Neopentecostal characteristic. For that, we have used as theoretical framework the French Line Discourse Analysis according Michel Pêcheux conceptualization, studied, interpreted and diffused by Eni Orlandi. We work with this theoretical framework for Neopentecostalism discursive forms analysis and subject and subjected identification.